The yak - Wiener, G.; Ruijun, L.; Han Jianlin (CRC Press, 2011)
The yak are the mainstay of livelihood for the nomads on the vast Qinghai-Tibetan Plateau of western China and adjacent regions. Yak withstand the extreme condition of a harsh, cold climate at high elevations. Numbers of yak in China are around 13 million. There are a number of recognized breeds, and microsatellite DNA markers have started to show some genetic distances between them. To improve productivity, yak can be hybridized with local or exotic cattle for use at lower elevation. The males of these hybrids are sterile. Crosses of domestic with wild yak show improved size and vigor. Traditionally, yak are managed in a transhumance system dictated by the seasons, but since the 1990s this system has been breaking down as herders are given ownership of animals and rights to parcels of rangeland. One calf every two years is the norm, and most usually not before three years of age. Body weight of adult females varies somewhat among breeds and situations but is around 220 kg (bulls reaching twice that). Yak females may lose 25% of their body weight over winter into early spring due to both low temperature and shortage of feed. For pregnant cows over that period, this can have unfavorable consequences for calf survival. Milk production is seasonal and averages among breeds from 150 to 500 kg with a fat content from 5.4% to 7.5%. Feces of yak are collected and dried for use as fuel. Fiber yields are variable (from 0.5 to 2.9 kg depending on breed and location), but the most valuable component is the down, representing about 60% of the total fleece in calves but substantially less in adults.